Investment in prickly pear: A promising opportunity in Algeria, with reference to the Egyptian experience - Hamid Mokrani (Journal of Excellence for Economics and Management Research, 2026)
The study aimed to highlight a promising investment opportunity in Algeria within the agricultural sector, where the country has enormous potential due to its large area and climate diversity, specifically the investment in the cultivation of prickly pear, given its significant economic and health importance.     Initially, we clarified the benefits of its fruit and the great economic value of the various parts of the prickly pear, as well as the reasons that make investing in the cultivation of this plant a promising opportunity in Algeria. We also highlighted the successful Egyptian experience in this field.     The study concluded that the Algerian climate is favorable for this investment, which is explained by the success of experiences conducted by Arab countries regarding prickly pear cultivation, whose landscapes are similar to those of Algeria. Moreover, prickly pear creates numerous jobs and generates considerable income with low costs, thereby increasing the added value of this type of investment. From a health perspective, it is considered a very beneficial food for humans, as well as a raw material for the extraction of medical products. Additionally, it is a good feed for livestock and is cultivated in certain regions as a windbreak or as a barrier against sand encroachment and desertification.